All urban areas’ energy use data across 640 districts in India for the year 2011 - Kangkang Tong; Ajay Singh Nagpure; Anu Ramaswami (Scientific Data, 2021)
Measurement(s) electrical energy • fossil fuel • energy use Technology Type(s) machine learning • statistical method Factor Type(s) end-use energy by activity sectors in cities Sample Characteristic - Environment city Sample Characteristic - Location India Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.13516925